Brachycephaly in French bulldogs and pugs is associated with narrow ear canals. Issue 3 (16th March 2022) - Töpfer, Tanja; Köhler, Claudia; Rösch, Sarah; Oechtering, Gerhard
Abstract : Background: Brachycephalic dog breeds have multiple skull malformations which may lead to anatomical changes in the external auditory canal. It is our frequent observation that in the otoscopic examination of the external ear in these breeds we are unable to visualise the tympanic membrane as a consequence of extreme narrowing of the proximal ear canal. Additionally brachycephalic dogs reportedly are predisposed to otitis externa (OE) and otitis media. Objectives: To characterizse the transition of the cartilaginous ear canal to the bony meatus acusticus externus using computed tomography (CT) and to investigate a possible association with OE in brachycephalic dogs. Materials and methods: Seventy‐five client‐owned dogs [pugs (n = 20), French bulldogs (n = 55)] were included and assessed for OE using an owner questionnaire and otoscopic and cytological examinations. In dorsal plane CT scans, the diameter of the porus acusticus externus was measured using novel methodology. The results were compared with a normocephalic control group without preexisting otological disorders. Results: Brachycephalic dogs had a significantly smaller porus acusticus externus diameter (2.6 mm) than normocephalic dogs (5.0 mm). Of the brachycephalic dogs, 32% had OE yet this was not statistically significantly related to the diameter of the porus acusticus externus. Middle ear effusion (44%) and narrowing of the external ear canal (82.6%) were significantly more frequent in brachycephalic dogs. Only five of 150 eardrums could be visualised otoscopically. Conclusions and clinical relevance: Malformation of the porus acusticus externus causes severe stenosis of the proximal ear canal in brachycephalic dogs. A connection between stenosis of the external auditory canal and OE could not be confirmed. Abstract : Background – Brachycephalic dog breeds have multiple skull malformations which may lead to anatomical changes in the external auditory canal. It is our frequent observation that in the otoscopic examination of the external ear in these breeds we are unable to visualise the tympanic membrane as a consequence of extreme narrowing of the proximal ear canal. Additionally brachycephalic dogs reportedly are predisposed to otitis externa (OE) and otitis media. Objectives – To characterizse the transition of the cartilaginous ear canal to the bony meatus acusticus externus using computed tomography (CT) and to investigate a possible association with OE in brachycephalic dogs. Conclusions and clinical relevance – Malformation of the porus acusticus externus causes severe stenosis of the proximal ear canal in brachycephalic dogs. A connection between stenosis of the external auditory canal and OE could not be confirmed. 摘要: 背景‐短头犬品种具有多发性颅骨畸形, 可能导致外耳道解剖变化。我们经常观察到, 在这些品种的外耳耳镜检查中, 由于近端耳道极度狭窄, 我们无法观察到鼓膜。此外, 据报告短头犬易患外耳炎(OE)和中耳炎。 目的‐使用计算机断层扫描(CT)观察软骨耳道向骨性外耳道的转变, 并研究短头犬OE与之可能存在的相关性。 材料和方法‐纳入75只客户拥有的犬[巴哥犬(n = 20), 法国斗牛犬(n = 55)], 并使用主人问卷以及耳镜和细胞学检查评估OE。在背侧平面CT扫描中, 采用新方法测量听孔外径。将结果与无既存耳病的头位正常对照组进行比较。 结果‐短头犬的听孔外径(2.6 mm)显著小于正常头犬(5.0 mm)。在短头犬中, 32%患有OE, 但这与外耳孔的直径无统计学显著相关性。中耳积液(44%)和外耳道狭窄(82.6%)在短头犬中明显较多。150个耳膜只有5个可以通过耳镜观察到。 结论和临床相关性‐外耳道畸形导致短头犬近端耳道严重狭窄。无法证实外耳道狭窄与OE之间的联系。 Résumé: Contexte ‐ Les races de chiens brachycéphales présentent de multiples malformations crâniennes qui peuvent entraîner des modifications anatomiques du conduit auditif externe. Nous observons fréquemment que lors de l'examen otoscopique de l'oreille externe chez ces races, nous sommes incapables de visualiser la membrane tympanique en raison d'un rétrécissement extrême du conduit auditif proximal. De plus, les chiens brachycéphales seraient prédisposés à l'otite externe (OE) et à l'otite moyenne. Objectifs ‐ Caractériser la transition du conduit auditif cartilagineux au méat osseux externe par tomodensitométrie (TDM) et étudier une éventuelle association avec l'OE chez les chiens brachycéphales. Matériels et méthodes ‐ Soixante‐quinze chiens de propriétaires [carlins (n = 20), bouledogues français (n = 55)] ont été inclus et évalués pour l'OE à l'aide d'un questionnaire du propriétaire et d'examens otoscopiques et cytologiques. Dans les tomodensitogrammes du plan dorsal, le diamètre du porus acusticus externus a été mesuré à l'aide d'une nouvelle méthodologie. Les résultats ont été comparés à un groupe témoin normocéphale sans trouble otologique préexistant. Résultats – Les chiens brachycéphales avaient un diamètre de porus acusticus externus significativement plus petit (2, 6 mm) que les chiens normocéphales (5, 0 mm). Parmi les chiens brachycéphales, 32 % avaient une OE, mais cela n'était pas statistiquement lié de manière significative au diamètre du porus acusticus externus . L'épanchement de l'oreille moyenne (44 %) et le rétrécissement du conduit auditif externe (82, 6 %) étaient significativement plus fréquents chez les chiens brachycéphales. Seuls cinq des 150 tympans ont pu être visualisés par otoscopie. Conclusions et pertinence clinique – La malformation du porus acusticus externus provoque une sténose sévère du conduit auditif proximal chez le chien brachycéphale. Un lien entre la sténose du conduit auditif externe et l'OE n'a pas pu être confirmé. Zusammenfassung: Hintergrund – Brachycephale Hunderassen haben multiple Missbildungen des Schädels, was zu anatomischen Veränderungen im äußeren Gehörkanal führen kann. Wir bemerken häufig, dass wir bei der otoskopischen Untersuchung des äußeren Gehörkanals dieser Rassen, das Trommelfell als Folge der extremen Verengung des proximalen Ohrkanals nicht einsehen können. Zusätzlich ist beschrieben, dass brachycephale Hunde zu Otitis externa (OE) und Otitis media (OM) prädisponiert sind. Ziele – Eine Darstellung des Übergangs vom knorpeligen Gehörkanal in den knöchernen Meatus acusticus externus mittels Computertomografie (CT) und eine Untersuchung über einen möglichen Zusammenhang mit der PE bei brachycephalen Hunden. Materialien und Methoden – Fünfundsiebzig Hunde in Privatbesitz [Möpse (n = 20), Französische Bulldoggen (n = 55)] wurden inkludiert und auf eine OE mittels BesitzerInnen Fragebogen, otoskopischer und zytologischer Untersuchung untersucht. In dorsalen planen CT Scans wurde der Durchmesser des Porus acusticus externus mittels neuer Methoden gemessen. Die Ergebnisse wurden mit einer normocephalen Kontrollgruppe ohne otologische Vorerkrankungen verglichen. Ergebnisse – Brachycephale Hunde haben einen signifikant kleineren Durchmesser des Porus acusticus externus (2, 6mm) als normocephale Hunde (5, 0mm). Von den brachycephalen Hunden hatten 32% eine OE, was aber mit dem Durchmesser des Porus acusticus externus statistisch nicht signifikant korreliert war. Ein Erguss im Mittelohr (44%) und eine Einengung des externen Gehörkanals (82, 6%) trat bei brachycephalen Hunden signifikant häufiger auf. Es konnten nur fünf von 150 Trommelfellen otoskopisch sichtbar gemacht werden. Schlussfolgerungen und klinische Relevanz ‐ Eine Missbildung des Porus acusticus externus verursacht eine gravierende Stenose des proximalen Ohrkanals bei brachycephalen Hunden. Es konnte kein Zusammenhang zwischen der Stenose des äußeren Gehörkanals und einer OE bestätigt werden. 要約: 背景 ‐ 短頭種の犬種は頭蓋骨の奇形が多く、外耳道の解剖学的変化をもたらすことがある。これらの犬種の外耳道検査では、近位外耳道が極端に狭窄しているために鼓膜を視認することができないことがしばしば観察される。また、短頭種は外耳炎や中耳炎になりやすいと言われている。 目的 – 本研究の目的は、CTを用いて軟骨性外耳道から骨性外耳道への移行を明らかにし、短頭種における外耳炎との関連性を検討することであった。 材料と方法‐オーナー所有犬75頭 (パグ (n = 20) 、フレンチブルドッグ (n = 55) ) を対象とし、飼い主アンケートと耳鏡検査および細胞診検査を用いて外耳炎を評価した。背面CTスキャンにおいて、新手法で外耳道孔の直径が測定された。その結果を、耳科疾患の既往のない正常な頭蓋を有する対照群との間で比較した。 結果‐短頭種の犬では、外耳道孔径が2.6mmと、正常頭種の犬 (5.0mm) より有意に小さかった。短頭種の犬のうち、32%が外耳炎を有していたが、統計学的に有意な耳孔径との関連は認められなかった。中耳炎 (44%) および外耳道狭窄 (82.6%) は短頭種の犬で有意に多くみられた。鼓膜を耳鏡で確認できたのは150頭中5頭のみであった。 結論と臨床的意義 ‐ 外耳道孔の奇形は、短頭種の犬において近位外耳道の重度の狭窄を引き起こす。外耳道狭窄と外耳炎の関連性は確認できなかった。 www.DeepL.com/Translator (無料版) で翻訳しました。 Resumo: Contexto – Raças de cães braquicefálicos apresentam múltiplas malformações cranianas que podem levar a alterações anatômicas no conduto auditivo externo. Frequentemente, observamos que na avaliação otoscópica da orelha externa destas raças não conseguimos visualizar a membrana timpânica como uma consequência do estreitamento extremo do conduto auditivo proximal. Além disso, cães braquicefálicos são sabidamente predispostos à otite externa (OE) e otite média. Objetivos – Caracterizar a transição do conduto auditivo cartilaginoso para o meato acústico ósseo externo utilizando tomografia computadorizada (TC) e investigar uma possível associação com OE em cães braquicefálicos. Materiais e métodos – Setenta cães de clientes [pugs (n=20), buldogues franceses (n = 55)] foram inclusos e avaliados para OE utilizando um questionário para os proprietários, citologia e otoscopia. Nas TCs em plano dorsal, o diâmetro do poro acústico externo foi mensurado utilizando uma metodologia nova. Os resultados foram comparados com um grupo de cães normocefálicos controle sem alterações otológicas pré‐existentes. Resultados – Os cães braquicefálicos apresentaram o diâmetro do poro acústico externo (2, 6mm) significativamente menor que os cães normocefálicos (5, 0mm). Dos cães braquicefálicos, 32% apresentavam OE, mas não houve relação significativa com o diâmetro do poro acústico externo. Presença de efusão na orelha média (44%) e estreitamento do conduto auditivo externo (82, 6%) foram significativamente mais frequentes em cães braquicefálicos. Apenas cinco de 150 tímpanos puderam ser visualizados por otoscopia. Conclusões e relevância clínica – Malformações do poro acústico externo causa estenose grave do conduto auditivo proximal em cães braquicefálicos. Não foi possível comprovar a conexão entre a estenose do conduto auditivo externo e OE. RESUMEN: Introducción ‐ las razas de perros braquicéfalos tienen múltiples malformaciones craneales que pueden provocar cambios anatómicos en el conducto auditivo externo. Con frecuencia observamos que en el examen otoscópico del oído externo en estas razas no podemos visualizar la membrana timpánica como consecuencia del estrechamiento extremo del conducto auditivo proximal. Además, según la literatura al respecto, los perros braquicéfalos están predispuestos a padecer otitis externa (OE) y otitis media. Objetivos – Caracterizar la transición del canal auditivo cartilaginoso al meato acusticus externus óseo mediante tomografía computerizada (CT) e investigar una posible asociación con OE en perros braquicefálicos. Materiales y métodos ‐ setenta y cinco perros de propietarios particulares [carlinos (n = 20), bulldogs franceses (n = 55)] fueron incluidos y evaluados por posible OE mediante un cuestionario para propietarios y exámenes otoscópicos y citológicos. En tomografías computerizadas del plano dorsal, el diámetro del porus acusticus externus se midió utilizando una metodología novedosa. Los resultados se compararon con un grupo control normocefálico sin trastornos otológicos preexistentes. Resultados ‐ los perros braquicefálicos tenían un diámetro del porus acusticus externus significativamente más pequeño (2, 6 mm) que los perros normocefálicos (5, 0 mm). De los perros braquicefálicos, el 32 % tenía OE, pero esto no se relacionó estadísticamente de manera significativa con el diámetro del porus acusticus externus. La efusión del oído medio (44 %) y el estrechamiento del conducto auditivo externo (82, 6 %) fueron significativamente más frecuentes en perros braquicefálicos. Solo cinco de 150 tímpanos pudieron visualizarse por otoscopia. Conclusiones y relevancia clínica – La malformación del porus acusticus externus causa estenosis severa del canal auditivo proximal en perros braquicefálicos. No se pudo confirmar una conexión entre la estenosis del conducto auditivo externo y la OE.